Budget System Reform in Transitional Economies : The Case of the Former Yugoslav Republics - Diamond, Jack.; Last, Duncan (Washington, D.C. : International Monetary Fund, 2003)
For the republics of the former Socialist Federal Republic of Yugoslavia (SFRY) as for many other transition economies, an important step in introducing a more market-oriented system was the restructuring of their budget systems. This paper reviews and evaluates the process of budget system reform during the transition period extending from the time they emerged from the collapse of the SFRY in 1989 until the end of 2002. For at least a decade of this period, the Fiscal Affairs Department of the IMF has been providing technical assistance (TA) to these countries to facilitate such reforms. Based on the material generated by this effort, the authors offer a review of the progress made and an assessment of the reform elements still to be completed. Given that the former Yugoslav republics all commenced the reform process with the same institutions, this paper offers a unique opportunity to analyze the critical elements in successful budget system reform. An attempt is made to explain the varying degrees of success experienced by different countries, and a reform agenda is suggested to guide future TA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet